2022
DOI: 10.1038/s41593-022-01131-4
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPRi/a platform in human iPSC-derived microglia uncovers regulators of disease states

Abstract: Microglia are emerging as key drivers of neurological diseases. However, we lack a systematic understanding of the underlying mechanisms. Here, we present a screening platform to systematically elucidate functional consequences of genetic perturbations in human induced pluripotent stem cell-derived microglia. We developed an efficient 8-day protocol for the generation of microglia-like cells based on the inducible expression of six transcription factors. We established inducible CRISPR interference and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 85 publications
0
98
0
Order By: Relevance
“…For the CROP-seq (pooled CRISPRi) screen, two iPSC lines were maintained at the University of California, San Francisco. For microglial differentiation, a transcription factor-based protocol (iTF-microglia) was used as described by Dräger et al (33). Similarly, neurons for the CROP-seq screen were generated using the transcription factor-based i 3 N approach as described by Tian et al (32).…”
Section: Genome Engineeringmentioning
confidence: 99%
“…For the CROP-seq (pooled CRISPRi) screen, two iPSC lines were maintained at the University of California, San Francisco. For microglial differentiation, a transcription factor-based protocol (iTF-microglia) was used as described by Dräger et al (33). Similarly, neurons for the CROP-seq screen were generated using the transcription factor-based i 3 N approach as described by Tian et al (32).…”
Section: Genome Engineeringmentioning
confidence: 99%
“…Disruption of nuclear architecture of progenitor cells has been observed [ 230 ]. The advent of CRISPR interference technology, which enables flexible targeting of genes upregulated in disease states [ 231 , 232 , 233 ], can be applied to target and limit abnormal activation of pathways discovered using in vitro models [ 234 ].…”
Section: Disease Modelingmentioning
confidence: 99%
“…One study has shown that overexpression of transcription factors CEBPA and PU.1 coupled with CNS-patterning molecules described above can generate Microglia-like cells from human iPSC ( Chen et al, 2021 ) with a second one showing improved efficiency by overexpressing PU.1 from primitive hematopoietic progenitors ( Sonn et al, 2022 ). A recent study has defined a set of six transcription factors for the generation of microglia-like cells at a scale sufficient for genetic screening ( Drager et al, 2022 ). Following the progress in the derivation of specific neuronal populations, it is plausible that newer approaches might find that just a few transcriptional factors could be sufficient, when coupled with small molecules, for the generation of this cell type.…”
Section: Glial Cellsmentioning
confidence: 99%